Environmentally-friendly trade policies to shape Mauritius' future - Jim de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Mauritius and other Small Island Development States (SIDS) depend heavily on international trade. This presents challenges to environmental management. SIDS are vulnerable to all forms of environmental degradation, of which part are related to international trade, the focus of this chapter. While climate change causes of environmental degradation are beyond the control of the government, others like deforestation, loss of biodiversity or degradation of their maritime and terrestrial environments including depletion of fish stocks in their Extended Economic Zones (EEZs) are, at least, partly, under their control.
Keywords: 330